Comparative evaluation of Egg Quality Parameters of Kadaknath and Vanaraja Chicken in Intensive Farming System - Pathak, SS; Tamuli, U; Khargaria, S; Bordolai, G; Khuman, LS; Chabukdhara, P; Gagoi, A; Rajbhogshi, P; Boruah, K (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
In the present study , a total of 60 eggs were assessed for egg quality parameters of Kadaknath and Vanaraja chicken reared under deep litter farming system . All chickens were provided uniform diet of Chick (0-8 weeks), Grower (9-20 weeks) and Layer (above 20 weeks) ration. Except for the shape index, the internal egg quality parameters were significantly (P<0.05) higher in Vanaraja eggs as compared to Kadaknath. Results revealed that the quality of egg of Vanaraja chicken was found to be better as compared to Kadaknath chicken. of Madhya Pradesh and in adjoining areas of Next to the cow milk egg is the only animal origin balanced food which is consumed and relished by majority of the population of the world (Baishya et al., 2008). In India, Per capita availability of eggs is only 69 while Indian Council of Medical Research recommendation is 182 (Amandeep Singh, 2018). The Kadaknath breed, also known as Kalamashi in Hindi, is known for its black-coloured meat. It is native of Jhabua and Dhar districts in the western region Gujarat and Rajasthan states (Valavan et al., 2016). The meat is known for its medicinal characteristics, fetching a higher demand among the consumers. Vanaraja, a dual purpose variety developed by Directorate of Poultry research, Hyderabad, India is highly popular among the rural people of Assam as one of the income generating source especially for the rural women. The success of poultry farming largely depends on the total number of good quality eggs